Pengaruh Latihan Leg Raise Terhadap Kekuatan Otot Perut Mahasiswa PKO UPRI - Arga Arga (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aims to determine the effect of leg raise exercises on abdominal muscle strength in students of the Sports Coaching Education Study Program at the University of Republic Indonesia. The research method used is an experiment with a pre-test post-test control group design. The sample consisted of twenty students divided into experimental and control groups. The experimental group underwent a leg raise training program for eight weeks, three times a week, while the control group received no special treatment. The instrument used to measure abdominal muscle strength was a sit-up test for sixty seconds. Data were analyzed using paired t-test and independent t-test with a significance level of zero point five. The results showed a significant increase in abdominal muscle strength in the experimental group after participating in the leg raise training program, with an average increase of twenty-nine point three percent. There was a significant difference between the experimental and control groups. Based on the results, it can be concluded that leg raise exercises positively affect the improvement of abdominal muscle strength in students of the Sports Coaching Education Study Program at the University of Republic Indonesia.